An investigation of demand and exchange rate shocks in the tourism sector. Issue 86 (9th April 2021) - Bozkurt, Kurtulus; Armutçuoğlu Tekin, Hatice; Can Ergün, Zeliha
Abstract : Purpose: This study aims to measure the relationship between demand and exchange rate shocks in the tourism industry. Design/methodology/approach: A panel data set is constructed covering the period between 1995 and 2017, and the data set includes the top 26 countries that host 10 million tourists and above in the world as of 2017. The standard errors of the series are used as an indicator of shocks. First, the cross-sectional dependency, stationarity and the homogeneity of the series are examined; second, a panel cointegration analysis is implemented; third, long-term panel cointegration coefficients are analyzed with Dynamic Common Correlated Effects (DCCE) approach; and, finally, Dumitrescu and Hurlin's (2012) Granger non-causality test is used to detect the causality. Findings: The preliminary analyses show that the variables are cross-sectional dependent and heterogeneous and are stationary in their first difference; hence, the effects of the shocks are temporary. On the other hand, as a result of the panel cointegration analysis, it is found that both series are cointegrated over the long-term. However, the long-term coefficients estimated with the DCCE approach are found not to be statistically significant. Finally, as a result of the Dumitrescu and Hurlin's (2012) Granger non-causality test, it is concluded that there is a causality running from exchange rate shocks to demand shocks. Originality/value: To the best of the authors' knowledge, the cointegration between the tourism demand shocks and exchange rates shocks has not been investigated before, and therefore, this study is considered to be a pioneering study that will contribute to the literature.